Therapeutic management for patients with trunk and extremities integumentary tissues defects of traumatic genesis - O. V. Ponomarenko (Zaporozhye State Medical University, 2017)
Objective: To improve the results of treating patients with wounds, functional and aesthetic defects of mechanical origin by developing a comprehensive program of surgery to restore the form and function of trunk and limbs. Materials and methods. The criteria for the inclusion into the study: both genders patients aged over 17 years with diagnosed skin and adjacent soft tissues of trunk and limbs defect that needed restoration of body form and functions. We have operated 231 patients with integumentary tissue defects of a mechanical origin in the clinic. There were 129 men, 102 women of them. The patients' age ranged from 17 to 76 years. Results. All the patients were divided into 4 groups depending on the size, depth and the extent of damage of soft tissues and other structures of the body and limbs. I group - 79 (34.2 %) patients with isolated soft tissues damage (to the fascia): 32 (13.85 %). II group - 67 (29 %) patients with injuries of integumentary tissues of a moderate severity whose vital activity was disturbed in a limited area with parawound zone (lower from fascia). III group - 48 (20.8 %) patients (tissues damage to a significant extent). IV Group - 37 (16 %) patients, whose trauma was accompanied by injury of a vascular-neural fascicle, partial or complete extremity abjunction. Conclusions. 1. The choice of corrective surgical intervention method and the closure of the integumentary tissue defect depended on the size, the depth of the wound and hemodynamic characteristics of the damaged area. 2. The new method of treating the consequences of traumatic injuries using the preparation of hyaluronic acid expanded the prospects of treating patients with integumentary tissues defects. 3. The differential approach to the choice of the method of closing the wound surfaces caused by mechanical damage made it possible to achieve satisfactory results in 97.84 % of cases.